2015
DOI: 10.1111/biom.12393
|View full text |Cite
|
Sign up to set email alerts
|

Population Size and Stopover Duration Estimation Using Mark–Resight Data and Bayesian Analysis of a Superpopulation Model

Abstract: We present a novel formulation of a mark-recapture-resight model that allows estimation of population size, stopover duration, and arrival and departure schedules at migration areas. Estimation is based on encounter histories of uniquely marked individuals and relative counts of marked and unmarked animals. We use a Bayesian analysis of a state-space formulation of the Jolly-Seber mark-recapture model, integrated with a binomial model for counts of unmarked animals, to derive estimates of population size and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(81 citation statements)
references
References 30 publications
2
79
0
Order By: Relevance
“…In this study, we extended the Bayesian superpopulation model developed by Lyons et al (2016) by accounting for heterogeneity in encounter and staying probabilities through finite mixtures in order to provide unbiased estimates of stopover timing, duration, and population size of migratory birds. Using a combination of analyses of simulated and real data, we showed that heterogeneity in encounter and staying probabilities is present in real datasets and can cause severely biased parameter estimates, especially of stopover duration and population size.…”
Section: General Conclusionmentioning
confidence: 99%
“…In this study, we extended the Bayesian superpopulation model developed by Lyons et al (2016) by accounting for heterogeneity in encounter and staying probabilities through finite mixtures in order to provide unbiased estimates of stopover timing, duration, and population size of migratory birds. Using a combination of analyses of simulated and real data, we showed that heterogeneity in encounter and staying probabilities is present in real datasets and can cause severely biased parameter estimates, especially of stopover duration and population size.…”
Section: General Conclusionmentioning
confidence: 99%
“…As our results in the Supplementary Material [Matechou and Caron (2017a)] demonstrate, these two values can be considerably different if the intervals between sampling occasions are long compared to the average stopover duration of individuals in the population. In addition, individuals that arrived but departed before the start of the study are also accounted for, which is not the case in, for example, Lyons et al (2016), who mention that, typically, studies at stopover sites are planned so that they start before most individuals have arrived. However, since phenology is changing in recent years, satisfying this criterion can become increasingly more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of individual arrival/departure times. Since we are estimating individual arrival and departure times, similar to Lyons et al (2016), we are able to estimate individual stopover durations as well as other statistics that are potentially of interest, such as number of individuals present at any time point. However, in contrast to Lyons et al (2016), we do not assign an arrival time of one to all individuals that were already present at the start of the study, as our mixture model allows us to extend arrival to times prior to the start of the study while accounting for the probability of remaining at the site until the start of the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations